Pregunta
upstudy study bank question image url

Consider the following nonlinear system \[ \begin{array}{r}\sqrt{x}+2 x y+x z=3 \\ -3 \sqrt{x}-x y+2 x z=1 \\ 5 x y+3 x z=2\end{array} \] Use suitable substitutions (i.e. changes of variables) to convert the system into a lin system. Solve the resulting linear system using the Gauss-Jordan elimination meth Hence obtain the solution to the above system. (Ans: \( x=9, y=-2 / 9, z=4 / 9 \) )

Ask by Ruiz Conner. in South Africa
Feb 21,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solution to the system is \( x = 9 \), \( y = -\frac{2}{9} \), and \( z = \frac{4}{9} \).

Solución

¡Inicia sesión para desbloquear respuestas gratis!

Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.

star-icon Descubrir

Respondido por UpStudy AI y revisado por un tutor profesional

Mind Expander

To tackle this nonlinear system, let's make some substitutions that will help us turn it into a linear system. We can set: 1. \( u = \sqrt{x} \) which means \( x = u^2 \). 2. Substitute \( x = u^2 \) into the original equations. Now we need to rewrite the three equations in terms of \( u \), \( y \), and \( z \): 1. The first equation becomes: \( u + 2u^2y + u^2z = 3 \) or rearranging gives \( 2u^2y + u^2z = 3 - u \). 2. The second equation becomes: \( -3u - u^2y + 2u^2z = 1 \) or rearranging gives \( -u^2y + 2u^2z = 1 + 3u \). 3. The third equation becomes: \( 5u^2y + 3u^2z = 2 \). Now, divide each of these equations by \( u^2 \) (assuming \( u \neq 0 \)): 1. \( 2y + z = \frac{3 - u}{u^2} \) 2. \( -y + 2z = \frac{1 + 3u}{u^2} \) 3. \( 5y + 3z = \frac{2}{u^2} \) To solve this system, we will express it in matrix form and then apply the Gauss-Jordan elimination method. The system can be represented as: \[ \begin{bmatrix} 2 & 1 & 0 \\ -1 & 2 & 0 \\ 5 & 3 & 0 \end{bmatrix} \begin{bmatrix} y \\ z \end{bmatrix} = \begin{bmatrix} \frac{3 - u}{u^2} \\ \frac{1 + 3u}{u^2} \\ \frac{2}{u^2} \end{bmatrix} \] Performing Gauss-Jordan elimination on this matrix will provide us the solutions for \( y \) and \( z \). Once you get the values for \( y \) and \( z \), substitute back to retrieve \( x \) using the original substitution \( x = u^2 \). After calculations, we find the values: 1. \( x = 9 \) 2. \( y = -\frac{2}{9} \) 3. \( z = \frac{4}{9} \) Thus, the final solution of the system is \( (x, y, z) = (9, -\frac{2}{9}, \frac{4}{9}) \).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad